Comparison of computed sonographic tomography and pulse-echo imaging in the head. - Dines, K A; Fry, F J; Patrick, J T; Gilmor, R L (American Journal of Neuroradiology, 1983)
Computed sonographic transmission tomograms of infant and adult human cadaver heads are presented and compared with sonographic pulse-echo and x-ray tomograms of the same horizontal planes. The sonographic attenuation tomograms were reconstructed from broadband transmission data obtained using the rotate/translate axial scan mode in much the same way as x-ray tomography is performed. The formalin-fixed infant cadaver head was scanned through the anterior fontanelle using pulse-echo and in a horizontal plane (3.3 cm superior to the Frankfort plane) using both pulse-echo (3.5 MHz and 5 MHz) and transmission sonography (5 MHz). The computed sonographic transmission tomogram revealed superior anatomic detail as compared with the pulse-echo images obtained in the horizontal plane and compared favorably with x-ray scans. The quantitative, noninvasive nature of sonographic tomography shows promise for clinical applicability in the infant. In the adult human cadaver, sonographic tomograms at 750 kHz are presented in both the transskull and excised brain conditions. These scans also offer promise for the possible clinical exploration of the method.